Towards sustainable architecture creation and evaluation practice: resource blindness phenomenon and chameleon principle - Augustinaitė, Dalia (Creativity Studies, 2025)
Sustainable meeting of human needs is contingent upon effective management of resources to address development challenges in qualitative manner, thereby engendering positive change. This issue concerns scientific verifiability of interaction between social and environmental capital. These settings provide the basis for development of universal theoretical framework to address principles of resource diversity in this study. The current study examines extent to which various sustainable development strategies – universal and specific documents, initiatives, collaborations and competitions, and sustainable development assessment systems – align with the aforementioned principles. Results are assumed to be in line with basic principles of art and innovation and therefore architecture, which are either ignored or endorsed. Resource blindness phenomenon and chameleon principle offer novel approaches to defining and explaining the ideas and characteristics of two distinct philosophies of creativity. The laws are crystallized through unprecedented methodology of reconciling natural and human capital characteristics through common and specific meanings described in scientific literature. Comprehensive spectrum of natures, states, types, and principles of sustainable interaction of resources thus formulated provides the universal theoretical framework. Appearance of the principles is then illustrated by architectural case study, thus defining criteria for sustainable interaction of resources in practice. Conclusions are given.